Taurine Reprograms Mammary-Gland Metabolism and Alleviates Inflammation Induced by Streptococcus uberis in Mice - Lan, Riguo; Wan, Zhixin; Xu, Yuanyuan; Wang, Zhenglei; Fu, Shaodong; Zhou, Yuanyuan; Lin, Xinguang; Han, Xiangan; Luo, Zhenhua; Miao, Jinfeng; Yin, Yulong (Frontiers in Immunology, 2021)
Streptococcus uberis (S. uberis) is an important pathogen causing mastitis，which causes continuous inflammation and dysfunction of mammary glands and leads to enormous economic losses. Most research on infection continues to be microbial metabolism-centric, and many overlook the fact that pathogens require energy from host. In this perspective, we uncover metabolic reprogramming during host immune responses is associated with infection-driven inflammation, particularly when caused by intracellular bacteria. Taurine, a metabolic regulator, has been shown to effectively ameliorate metabolic diseases. We evaluated the role of taurine in the metabolic regulation of S. uberis-induced mastitis. Metabolic profiling indicates that S. uberis exposure triggers inflammation and metabolic dysfunction of mammary glands and mammary epithelial cells (MECs, the main functional cells in mammary glands). Challenge with S. uberis upregulates glycolysis and oxidative phosphorylation in MECs. Pretreatment with taurine restores metabolic homeostasis, reverses metabolic dysfunction by decrease of lipid, amino acid and especially energy disturbance in the infectious context, and alleviates excessive inflammatory responses. These outcomes depend on taurine-mediated activation of the AMPK–mTOR pathway, which inhibits the over activation of inflammatory responses and alleviates cellular damage. Thus, metabolic homeostasis is essential for reducing inflammation. Metabolic modulation can be used as a prophylactic strategy against mastitis.